REFORMS OF HIGHER EDUCATION AND INTERNATIONAL COOPERATION IN THE KHOREZM REGION DURING THE YEARS OF INDEPENDENCE (Conferencea, 2022)
This article analyzes the development of the higher education system in our country during the years of independence, its organizational legal basis, adopted normativelegal documents, implementation of international cooperation programs in Khorezm region and practical results.